1999
DOI: 10.5089/9781451842029.001
|View full text |Cite
|
Sign up to set email alerts
|

Central Bank Autonomy, and Inflation and Output Performance in the Baltic States, Russia, and Other Countries of the Former Soviet Union, 1995-1997

Abstract: A higher degree of de jure autonomy and accountability of the central banks of the Baltic states, Russia, and other countries of the former Soviet Union appears to be positively correlated with lower average inflation. There also seems to be some positive correlation between greater central bank autonomy and higher average real growth, after the initial period of reforms. Central banks with a higher degree of autonomy and accountability have apparently also reformed their operations more aggressively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
(22 reference statements)
2
37
0
Order By: Relevance
“…Moreover, the more detailed index (with sub-characteristics for each variable) must be supported by a weighting system and a subjective judgement is involved in choosing the characterization of variables and the weights in aggregation. Table 2 presents rankings of central bank independence according to three indices: GMT built for the purpose of this paper, Cukierman et al (1998) (CMN) and Lybek (1999). Since Lybek's study covers only FSU countries, the FSU and the Central European banks are compared separately.…”
Section: The Index Of Central Bank Independence and Comparison With Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the more detailed index (with sub-characteristics for each variable) must be supported by a weighting system and a subjective judgement is involved in choosing the characterization of variables and the weights in aggregation. Table 2 presents rankings of central bank independence according to three indices: GMT built for the purpose of this paper, Cukierman et al (1998) (CMN) and Lybek (1999). Since Lybek's study covers only FSU countries, the FSU and the Central European banks are compared separately.…”
Section: The Index Of Central Bank Independence and Comparison With Pmentioning
confidence: 99%
“…The CMN index does not cover the position of the board. Cukierman et al (1998), Lybek (1999. As previously, the year indicates the year of the latest amendment to the law.…”
Section: The Index Of Central Bank Independence and Comparison With Pmentioning
confidence: 99%
“…Loungani and Sheets (1997) have established that the central bank independence in transition conditions negatively influences inflation rate, which has also been established by Cukierman (1998), whereas he pointed out necessity for economic liberalization of adequate level. Lybek (1999) has researched connection of the central bank independence and certain macro-economic indicators in former Soviet countries, whereas he included elements of the accountability of the central banks into the model designed for measuring of the independence. His model is more rigorous than Cukiermans's or GMT model, in order to be less influenced by subjective elements when applied.…”
Section: Theoretic Considerations and Researches Of The Central Bank mentioning
confidence: 99%
“…By researching actual CBI, the authors concluded that some of the countries were still not free from the political interference. Lybek (1999) used as a measurement an index which constituted 21 indicators, including the elements of measuring central banks' responsibility. The author has established that countries with higher levels of de jure independence and the responsibility of the respective central banks have lower inflation rates in the period -1997.…”
Section: Theoretical Attitudes On the Cbi And An Outline Of The Empirmentioning
confidence: 99%